COMPARATIVE STUDY OF ERP IMPLEMENTATION METHODOLOGY CASE STUDY: ACCELERATED SAP VS DANTES & HASIBUAN METHODOLOGY - Muhammad Hafizhuddin Hilman; Farisya Setiadi; Ika Sarika; Jarot Budiasto; Rakhmat Alfian (Jurnal Sistem Informasi, 2012)
Enterprise Resource Planning (ERP) system is a concept of enterprise system that describe the integration of the whole process in the organization. Study in this field mostly about external development paradigm on information system development. So, issue in ERP is all about how to adopt it in the organization, not about the application development. This paper reviews two methodology on ERP system implementation, one is vendor perspective methodology and new generic perspective methodology. Comparation of both methodology is done in this study by using Roger Sessions’ metric. Result is the vendor perspective slightly superior than the new generic perspective methodology.